2017
DOI: 10.5194/hess-21-6461-2017
|View full text |Cite
|
Sign up to set email alerts
|

Does nonstationarity in rainfall require nonstationary intensity–duration–frequency curves?

Abstract: Abstract. In Canada, risk of flooding due to heavy rainfall has risen in recent decades; the most notable recent examples include the July 2013 storm in the Greater Toronto region and the May 2017 flood of the Toronto Islands. We investigate nonstationarity and trends in the short-duration precipitation extremes in selected urbanized locations in Southern Ontario, Canada, and evaluate the potential of nonstationary intensity-duration-frequency (IDF) curves, which form an input to civil infrastructural design. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 135 publications
(169 reference statements)
3
67
0
Order By: Relevance
“…A station is considered as nonstationary for a given duration category if consistent significant trends are obtained for all analysed series across study periods or significance levels (α). Change point detection in the rainfall series is also analysed using Pettitt's (1979) test (e.g., Ganguli & Coulibaly, 2017) with the aim of identifying stations with potential data irregularities. All rainfall series with at least 20 years of data (e.g., Figure 2a was not to perform a comparison of trends across stations, for which a common study period with few missing data for all analysed series would be ideally considered (e.g., Khaliq et al, 2009).…”
Section: Nonstationary Stationsmentioning
confidence: 99%
“…A station is considered as nonstationary for a given duration category if consistent significant trends are obtained for all analysed series across study periods or significance levels (α). Change point detection in the rainfall series is also analysed using Pettitt's (1979) test (e.g., Ganguli & Coulibaly, 2017) with the aim of identifying stations with potential data irregularities. All rainfall series with at least 20 years of data (e.g., Figure 2a was not to perform a comparison of trends across stations, for which a common study period with few missing data for all analysed series would be ideally considered (e.g., Khaliq et al, 2009).…”
Section: Nonstationary Stationsmentioning
confidence: 99%
“…In these cases, the use of the more complex nonstationary model may not be justified as the predictions of both models are similar. Similar conclusions were also obtained in Ganguli and Coulibaly (2017), where despite the presence of nonstationary signals in short-duration rainfall extremes, statistically indistinguishable differences were obtained between stationary and nonstationary return level estimates.…”
Section: Discussionmentioning
confidence: 99%
“…They stressed out the importance of a fair comparison of the models through the assessment of sampling uncertainties. Ganguli and Coulibaly () investigated nonstationarities and trends in short‐duration precipitation extremes in selected urbanized locations in Southern Ontario, Canada, and indicated that the nonstationarity signature in rainfall extremes does not necessarily imply the use of nonstationary IDFs for design purposes. Ganguli and Coulibaly () used RCP8.5 scenario projections for the same study area and found a significant increase in shorter return levels using both stationary and nonstationary frequency analysis methods and a detectable trend was noted for longer return period estimates.…”
Section: Introductionmentioning
confidence: 99%
“…There is no general consensus about the influence of global warming on local precipitation regimes. For some authors, the physical consequence of temperature rise is the general increase in precipitation extremes due to the increase in atmospheric water retention (Bao, Sherwood, Alexander, & Evans, ; Barbero, Fowler, Lenderink, & Blenkinsop, ; Ganguli & Coulibaly, ; Tsanis, Koutroulis, Daliakopoulos, & Jacob, ); for others, such a correlation could be deeply influenced by local features or counter‐feedbacks (e.g., soil–water availability; Panthou et al, ). However, several studies in the Mediterranean area, which is considered a “hot spot” for climate change (Giorgi, ; Giorgi & Lionello, ), showed that an increase in the frequency of extreme events should be expected, often associated with a reduction in rainfall total volumes (Bucchignani, Montesarchio, Zollo, & Mercogliano, ; Chiew et al, ; Ntegeka, Baguis, Roulin, & Willems, ; Zollo, Rillo, Bucchignani, Montesarchio, & Mercogliano, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the framework of climate change, extreme value analysis is usually undertaken with two different approaches. One approach consists in the statistical analysis of historical data, looking for trends in significant indicators such as mean value, moments, and probability distributions (Ganguli & Coulibaly, 2017;Markonis, Batelis, Dimakos, Moschou, & Koutsoyiannis, 2017). The second approach relies on the availability of climate projections providing estimates of future trends under different GHGs' concentration scenarios (DeGaetano & Castellano, 2017;Fadhel, Rico-Ramirez, & Han, 2017;Rodriguez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%